Cempaka Wilis Dalam Datuaaji Janantaka (Kajian Teks Dan Aktualisasinya Dalam Kehidupan Masyarakat) - Ida Ayu Oka Suryantari; I Wayan Suarjaya; Ni Komang Sutriyanti (Kamaya: Jurnal Ilmu Agama, 2019)
The planting of life values ​​contained in literature is well known and understood by society. One satua containing the values ​​of Hindu religious teachings is satua Aji Janantaka. Satua Aji Janantaka has a uniqueness, that Cempaka Wilis in the satua should not be used because pertained taru are still leteh (dirty). The reality in society is very different, Cempaka Wilis is still used and Cempaka Wilis interest is traded. The research is located in Kamasan village, Klungkung district, Klungkung regency. Given the village of Kamasan is a tourist village located in urban areas and the mascot of Klungkung district is cempaka flowers. Based on the background of the problem, then there are some formulation of the problem, namely: (1) How is the structure of narrative text satya Aji Janantaka? (2) What educational value is contained in Aji Janantaka's text? (3) How is the actualization of Cempaka Wilis usage in community life in Kamasan Klungkung village? The basic concepts in this research are Cempaka Wilis, satua Aji Janantaka, text, actualization, and Kamasan village. Theories used are: (1) Narrator Structuralism Theory (2) Value theory (3) Theory of symbolic interactionism. Metedologi in this research that is: The research type is qualitative. The location of this research is in Kamasan Klungkung village. The type of data in this study is qualitative research. The data source of this research is primary data and secondary data. Instruments in this study are the researchers themselves, interview guides and tools. The method of determining informants using snownball sampling. Methods of data collection using observation techniques, interviews, documentation and literature study. Data analysis techniques by data reduction, classification, display and interpretation. The research results include Narrative Structure tek a) figures and characterizations covering the main character is Prabu Partipa and the heroine is Betara Darma, subordinate figure in the form of the patih and wooden tree. b) there are seven major incidents in the Aji Janantaka. c) The text flow uses a straight path. d) Background covers place, time and atmosphere. e) Key themes cover the ethics of wood use, and additional themes include the sanctity of mind. f) The language style used by contrast and comparison. g) The message or message is to keep the purity of the self and the main source of everything is the mind. The values ​​contained in Satua Aji Janantaka's text include: a) Religious values ​​b) Aesthetic value c) Ethical values ​​d) Sradha and Bhakti value. Actualization of Cempaka Wilis in Kamasan Village community, namely: a) Understanding of Kamasan people to Satua Aji Janantaka text is very minimal so there are still many people who use Cempaka Wilis. b) The use of Cempaka Wilis in Kamasan Village is still mostly found in making upakara yajña, building houses and holy places.